Pengaruh Financial Technology, Risk Tolerance, Return Expectation, dan Financial Literacy terhadap Keputusan Investasi Mahasiswa pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Budi Luhur Jakarta - Fiqri Ramadhan; Said Said (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of financial technology, risk tolerance, return expectation, and financial literacy on student investment decisions, with a specific focus on students of the Faculty of Economics and Business, Budi Luhur University, Jakarta. The increasing growth of young investors in Indonesia, particularly from Generation Z, emphasizes the urgency of understanding the behavioral and technological factors that shape their financial decision-making. The research employed a quantitative approach using purposive sampling by distributing online questionnaires to 100 executive class students, calculated using Slovin’s formula. Data collection was supported by literature reviews and documentation, while analysis was conducted using multiple linear regression with the help of SPSS version 26 and Microsoft Excel 2019. The results reveal that financial technology, return expectation, and financial literacy each have a positive and significant effect on student investment decisions. In contrast, risk tolerance shows a significant negative effect, suggesting that higher risk tolerance does not necessarily translate into better decision-making among students. These findings highlight the complex interplay of behavioral and cognitive factors in shaping investment choices. The study contributes to the field of behavioral finance and provides practical implications for financial education, suggesting the need for stronger integration of financial literacy programs and responsible fintech usage among young investors. In conclusion, enhancing financial knowledge and aligning return expectations are critical strategies to improve rational investment behavior in the digital era.